Meningkatkan kemampuan membaca melalui permainan bangun kata pada anak kelompok B di TK Dharma Wanita Persatuan 2 Gubuklakah - Sholikha, Siti; Haryono , Sarah Emmanuel; Asmah, Ayu (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Widya Gama Mahakam Samarinda, 2026)
Reading skills are one of the basic skills that are very important for early childhood development. Reading for early childhood is closely related to language development. Many early childhood still have difficulty in developing reading skills, especially in recognizing letters and arranging words. This research aims to improve early childhood reading skills through the application of word building games at Dharma Wanita Persatuan 2 Kindergarten, Gubuklakah, Malang Regency. This research uses a Class Action Research (PTK) approach with two cycles, each consisting of several stages, namely planning, action, observation, and reflection. The word building game is carried out using media in the form of letter cards, object pictures, and loose parts. The results of the study show that through the application of this game, there is a significant increase in children's early reading skills. In the first cycle, the average result reached 43.3%, while in the second cycle it increased to 75.8%, which shows that word building games are effective in improving children's early reading skills at Dharma Wanita Persatuan 2 Gubuklakah Kindergarten.